Positive Thinking as a Mediator in the Relationship Faith and Resilience in Students Who Are Working on a Thesis - Muslimin, Zidni Immawan; Pihasniwati, Pihasniwati; Widuri, Erlina Listyanti; Anilon, Basir Jarah (Universitas Muhammadiyah Yogyakarta, 2025)
Students who are working on a thesis include individuals who are vulnerable to experiencing mental disorders due to the heavy burden and demands of the thesis. In facing these challenges, students need resilience skills to complete the thesis process successfully. This correlational study aims to determine the relationship between faith and resilience in students completing a thesis, with positive thinking as a mediator. The subjects of this research were undergraduate students at universities in the Special Region of Yogyakarta who were preparing a thesis with a study period of more than 7 semesters, totaling 99 respondents. In this study, three scales were used: the scale of faith, whose aspects were taken from Al Banna, with a reliability coefficient of 0.927; the positive thinking scale, which refers to the aspects of Albercht's opinion, with a reliability coefficient of 0.949, and the resilience scale, which refers to the aspects of Grotberg, with a reliability coefficient of 0.944. Hypothesis testing was conducted using mediation regression analysis with the Jamovi program (version 2.3). The results showed that aqeedah (faith) positively affected positive thinking in students completing their thesis. Positive thinking had a significant positive effect on resilience. Directly, aqeedah positively affected resilience, indicating that positive thinking could partially mediate the relationship between faith and resilience.